Temporary mechanical support in fulminant myocarditis: prognostic factors and clinical implications from the FULLMOON study - Schmidt, Matthieu; Ponnaiah, Maharajah; Huang, Florent; Montero, Santiago; Raimbault, Victor; Abrams, Darryl; Lebreton, Guillaume; Pellegrino, Vincent; Ihle, Joshua; Bottiroli, Maurizio; Persichini, Romain; Barrionuevo-Sánchez, M Isabel; et al. (Intensive care medicine, 2026)
BACKGROUND: Temporary mechanical circulatory support (t-MCS) is increasingly used in fulminant myocarditis (FM), yet long-term outcomes and risk factors remain poorly defined. METHODS: From the FULLMOON international cohort (419 adults with suspected FM across 36 centers in 15 countries), 295 patients treated with venoarterial extracorporeal membrane oxygenation (V-A ECMO) and/or Impella were analyzed. The primary endpoint was mortality at 1 year, heart transplantation (HTx), or left-ventricular assist device (LVAD). Multivariate Cox regression identified predictors of adverse outcomes. A propensity score-weighted analysis assessed outcomes based on timing of endomyocardial biopsy (EMB): early (≤ 2 days), delayed (> 2 days), or none. RESULTS: The median age was 39 years (IQR 28-60), and 55% were female. Myocarditis was confirmed in 204 (69%) of the patients via histology or cardiac MRI. Histological data were available for 151 (51%) of the cohort. One-year mortality was 36%, while 44% died or had an HTx or LVAD. Predictors of worse outcomes were giant cell myocarditis, older age, cardiac arrest at ECMO initiation, and delayed EMB. Delayed EMB was consistently associated with higher mortality, HTx, or LVAD compared to early (HR = 1.55; 95% CI 1.23-1.96; p < 0.01) or no EMB (HR = 1.59; 95% CI 1.26-2.01; p < 0.01). However, event-free survival did not differ significantly between early EMB and no EMB (HR = 1.03; 95% CI 0.80-1.32; p = 0.85). CONCLUSIONS: Despite a relatively young cohort, FM requiring t-MCS is associated with a high 1-year mortality rate. Timely recognition and early referral to specialized ECMO centers before cardiac arrest are critical.
Keywords: Endomyocardial biopsy; Temporary mechanical support; ECMO; Outcomes; Fulminant myocarditis